-3+6x=-4x-23

Simple and best practice solution for -3+6x=-4x-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+6x=-4x-23 equation:


Simplifying
-3 + 6x = -4x + -23

Reorder the terms:
-3 + 6x = -23 + -4x

Solving
-3 + 6x = -23 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-3 + 6x + 4x = -23 + -4x + 4x

Combine like terms: 6x + 4x = 10x
-3 + 10x = -23 + -4x + 4x

Combine like terms: -4x + 4x = 0
-3 + 10x = -23 + 0
-3 + 10x = -23

Add '3' to each side of the equation.
-3 + 3 + 10x = -23 + 3

Combine like terms: -3 + 3 = 0
0 + 10x = -23 + 3
10x = -23 + 3

Combine like terms: -23 + 3 = -20
10x = -20

Divide each side by '10'.
x = -2

Simplifying
x = -2

See similar equations:

| (4/3)x+(1/2)=(-5/2) | | 4(-3x+1)=-2(7x-5) | | 4y-2+y+23=7y+30-5y | | 23+n+6=34 | | 8/y+7=5/y | | (5/8)x-(3/2)=12 | | 9=-5v+7 | | 7.6x-2.3x=-95.4 | | 7+8x=2-5x | | (3/4)x-(1/2)=(1/4) | | -5+4n-7=8 | | 3(3x-4)+5x= | | (2/5)x-(1/5)=(3/5) | | -1/3x+2=4 | | 5/6d=3/15 | | 16x^2+8x-64=0 | | 8-12v-9v= | | 5x+12=7x+20 | | 2k-5/-5 | | 6x-(3x+8)=4x-43 | | 0.70x+0.05(4-x)=0.10(106) | | 5x^2+7x+20=7x^2+3-10 | | -327/180 | | 4x-44y=32 | | 4(4x^2+7x-1)= | | (4x+3)2=68 | | 4x+3(x-5)=2x+3 | | 5x/5=25 | | 30x+10=4x-5 | | 16x-7=5-14x | | 24=-5p-p | | 15+9+2x=x |

Equations solver categories